2007
DOI: 10.1016/j.biocel.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic and ER J-domains of mammalian and parasitic origin can functionally interact with DnaK

Abstract: Both prokaryotic and eukaryotic cells contain multiple heat shock protein 40 (Hsp40) and heat shock protein 70 (Hsp70) proteins, which cooperate as molecular chaperones to ensure fidelity at all stages of protein biogenesis. The Hsp40 signature domain, the J-domain, is required for binding of an Hsp40 to a partner Hsp70, and may also play a role in the specificity of the association. Through the creation of chimeric Hsp40 proteins by the replacement of the J-domain of a prokaryotic Hsp40 (DnaJ), we have tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…Several other reports have analyzed the effects of overexpression of the J domains of cognate or non-cognate JDPs in related/divergent model systems (13,62,63), but rarely has the specific impact of the JDP substrate-binding domain been investigated. Our data, together with those of others, reveal novel insights into the biology of DnaJ family proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Several other reports have analyzed the effects of overexpression of the J domains of cognate or non-cognate JDPs in related/divergent model systems (13,62,63), but rarely has the specific impact of the JDP substrate-binding domain been investigated. Our data, together with those of others, reveal novel insights into the biology of DnaJ family proteins.…”
Section: Discussionmentioning
confidence: 99%
“…PFD0462w (PfJ1, PfDnaJA) has been shown to display increased mRNA and protein levels upon heat shock (16,17). Heterologous complementation studies have revealed that replacing the bacterial J-domain of a thermosensitive E. coli strain (OD259) with the J-domain from PFD0462w could reverse the thermosensitivity of these bacteria in vivo (17).…”
Section: Type I Hsp40smentioning
confidence: 99%
“…Heterologous complementation studies have revealed that replacing the bacterial J-domain of a thermosensitive E. coli strain (OD259) with the J-domain from PFD0462w could reverse the thermosensitivity of these bacteria in vivo (17). This indicated that these plasmodial J-domains were able to specifically interact with E. coli Hsp70 (DnaK).…”
Section: Type I Hsp40smentioning
confidence: 99%
“…Amino acid codons used most frequently in P. falciparum are different to those used by other organisms [10]. Experimental strategies that have been adopted in order to overcome these obstacles include: rare codon tRNA supplementation [11], codon optimization [10,12] and codon harmonization [13].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was used successfully for the production of full-length P. falciparum heat shock protein 70 (PfHsp70) [14]. Codon optimization is an experimental strategy in which the coding region of a target protein is designed to include the most frequently used codons of the host cell [12]. However, the expression of many malaria proteins was not improved through codon optimization [15].…”
Section: Introductionmentioning
confidence: 99%